PENGGUNAAN BIOLOGICAL EFFECTIVE DOSE DALAM MENENTUKAN KOMPENSASI JADWAL FRAKSINASI BARU PADA KANKER KEPALA DAN LEHER - Buddy Martin Mulya, Limbong
The main principle of radiotherapy is to give the maximum dose to cancer cells and the minimum dose to normal cells. Although the main purpose of radiotherapy is to kill cancer cells, the safety of the Organ at Risk (OAR) around the cancer cells must also be a concern during radiotherapy. One of the radiotherapy that is often used to kill cancer cells is fractionation. However, during the fractionation treatment period there is a possibility of disturbance. This disturbance can cause a pause in the middle of the treatment period so that it has the potential to frustrate the entire fractionation process. To overcome this problem, a derivative of the linear quadratic mathematical model (LQ), namely Biological Effective Dose (BED) is used. However, in the case of the addition of the total fractionation time, this BED equation cannot be used immediately. That is because there is a repopulation factor that must be considered if there is an increase in the total time of fractionation treatment. The BED equation will then be modified by adding a repopulation factor to it. By adding the repopulation factor, a significantly different BED value is compared to the BED value obtained from the previous BED equation. The difference in the value of BED can affect the success of radiotherapy that is being done. Therefore, the repopulation factor is an important factor that must be considered in overcoming disruptions that occur during the fractionation process. In addition, the repopulation factor must also be considered in planning a new fractionation process so that the new plan can successfully kill cancer cells as previously planned.